Occupational Chemical Exposure and Risk Assessment among Workers in Power Plant Process, Rayong Province, Thailand - Chaiprakarn, Somboon; Sakulthaew, Chanakarn; Ratcha, Mongkol; Saengseedam, Panudech (Universitas Airlangga, 2025)
Introduction: The combined cycle power plant involves the use of highly hazardous chemicals, primarily utilized in water quality improvement processes and cooling systems. Employees are susceptible to potential health risks associated with exposure through inhalation, skin, and eye contact. This study aims to assess the risk of chemical exposure among employees in the power plant process. Methods: The analysis uses secondary data collected from chemical measurements in the workplace environment during the power plant's three-years of operation. Results: The analysis identified hydrogen peroxide, sodium hydroxide, sulfuric acid, and hydrochloric acid as commonly utilized in power plant operations, with exposure occurring primarily through inhalation. While industrial hygiene assessments over the past three years reported atmospheric concentrations below standard limits, health risk assessments highlighted these chemicals as presenting unacceptable but manageable risks to employee health. Furthermore, the presence of mutagenic and highly carcinogenic compounds was observed. Especially, exposure surveillance has not yet been incorporated into the production process for risk evaluation. Conclusion: Therefore, the results of the risk assessment indicate that exposure should be monitored by conducting industrial hygiene measurements for highly hazardous chemicals and conducting employee health risk assessments, as required by law, for all types of hazardous chemicals.